2017
DOI: 10.1182/blood-2017-04-778993
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulants for treatment of HIT: update of Hamilton experience and literature review

Abstract: Key Points New data plus a literature review documented new thrombosis in only 1 (2.2%) of 46 patients with acute HIT who were treated with rivaroxaban. The literature review found similarly favorable results, albeit with fewer patients, when apixaban and dabigatran were used to treat acute HIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
146
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(154 citation statements)
references
References 52 publications
1
146
0
7
Order By: Relevance
“…Among the 12 patients who received dabigatran for HIT management, only 1 patient had a possible thrombotic event while receiving a DOAC (multiple strokes, which might have been present before starting dabigatran). None of the patients experienced major hemorrhagic events …”
Section: Discussionmentioning
confidence: 98%
“…Among the 12 patients who received dabigatran for HIT management, only 1 patient had a possible thrombotic event while receiving a DOAC (multiple strokes, which might have been present before starting dabigatran). None of the patients experienced major hemorrhagic events …”
Section: Discussionmentioning
confidence: 98%
“…Despite the low quality of evidence, fondaparinux has still gained wide‐spread acceptance as a treatment option for HIT 6. A similar phenomenon is currently happening with direct oral anticoagulants (DOACs) 29. Oral administration gives DOACs an advantage over fondaparinux, however, there will always be a role for a parenteral agent that can be given to HIT patients who are too sick to take oral agents.…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature review suggested that DOACs are highly efficacious in this scenario, although most patients included in the report were treated with rivaroxaban 3. Among DOACs, apixaban is the least dependent on renal clearance of the direct factor Xa inhibitors and might be the one with the smallest bleeding risk 4.…”
Section: Discussionmentioning
confidence: 99%